Short-term supplementation of DHA as phospholipids rather than triglycerides improve cognitive deficits induced by maternal omega-3 PUFA deficiency during the late postnatal stage. Issue 2 (16th December 2020) - Wen, Min; Zhao, Yingcai; Shi, Haohao; Wang, Chengcheng; Zhang, Tiantian; Wang, Yuming; Xue, Changhu
Abstract : Cognitive deficiencies caused by maternal omega-3 PUFA deficiency (O-3 Def), are easier reversed when supplementation of DHA as phospholipids than triglycerides, especially during the late postnatal stage. Abstract : Cognitive deficiencies, which are caused by maternal omega-3 PUFA deficiency (O-3 Def), are likely to be more rapidly and easily reversed at younger ages with quicker DHA reversal. This study aims to compare the efficiency of short-term supplementation of DHA in the form of phospholipids (PL) and triglycerides (TG) and improve cognitive deficiency in the O-3 Def model during different periods of brain development (3-week and 7-week old). The animal's spatial task performance, brain PUFA concentration, histopathology, and expression of synapse-associated proteins in the hippocampus were then analyzed. We demonstrate here that DHA-PL shows improved efficiency in improving cognitive deficiency compared to DHA-TG, particularly for adult O-3 Def offspring. The superiority of DHA-PL also correlates with the specific elevation of synapse-associated proteins, including BDNF, DCX, GAP-43, Syn, and PSD95, except to higher brain DHA accretion. This work highlights the DHA-PL as a better DHA supplement for inferior brain development caused by maternal O-3 Def, especially regarding those who missed the optimal time window of neurodevelopment.